(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Effective speaking skills are essential for personal and professional success in today’s fast-paced, interconnected world. This article explores advanced strategies to enhance verbal communication, focusing on the intricacies of articulation, non-verbal cues, and audience engagement. We delve into the importance of clarity and coherence in speech, emphasizing techniques such as structured argumentation and persuasive rhetoric. Additionally, we examine the role of active listening in fostering meaningful dialogue and building rapport with listeners. The article also highlights the significance of practice and feedback in refining speaking abilities, offering practical exercises and resources for continuous improvement. By integrating these advanced methodologies, individuals can elevate their speaking proficiency, ultimately leading to more impactful interactions and presentations in diverse contexts.